Synthesis of nanocrystalline barium titanate: Effect of microwave power on phase evolution. Issue 12 (September 2020) - Venkatachalam, Vinothini; Vaidhyanathan, Balasubramaniam; Binner, Jon
Graphical abstract: Abstract: Nanocrystalline BaTiO3 (BT) powder was synthesised using a polymer precursor route and the influence of conventional, microwave and combined hybrid heating methods on phase formation was investigated. A single-phase tetragonal BT (t-BT) nanocrystalline powder of about 20 nm primary particle size and decreased agglomeration were formed when high levels of microwave energy were used. This was accomplished at a lower processing condition of 700 °C for 30 min compared to conventional processing, which required 900 °C for 5 h, resulting in potential savings in time and energy. During the nano BT synthesis, the role of microwaves was determined by subjecting the samples to identical thermal histories, i.e. exactly the same time-temperature profiles, while using a range of different levels of microwave power. Significant reduction in the activation energy for the formation of the tetragonal phase was observed with increasing levels of microwave power and the results are explained in terms of a possible non-thermal mechanism. Furthermore, under otherwise identical thermodynamic conditions of temperature, time and (atmospheric) pressure, the co-occurrence of hexagonal crystal structure at < 200 W of additional microwave power along with formation of tetragonal crystal structure at ≥ 200 W and single phase tetragonal crystal structure at ∼1200 W was observed, demonstrating a new method of controlling the phase evolution during the synthesis of nanostructured barium titanate powder. The methodology could be applied to synthesise a variety of functional ceramic powders with tailored levels of crystallographic phases.